Students’ Mathematical Problem Solving Abilities: The Impact of The Co-Op Co-Op Cooperative Learning Model and Missouri Mathematics Project - Sunanto, Rahma Faelasofi; Apriliani, Risna; Nafi'ah, Walidatul (Universitas Islam Negeri Raden Intan Lampung, 2020)
The development of the industrial revolution must be balanced by the increase of quality soft skills, one of which is problem-solving ability. This study was aimed to determine which learning models that have more influence on students' mathematical problem-solving abilities. Cooperative learning model Co-Op Co-Op with students who applied the Missouri Mathematics Project learning model. This research employed the quasi-experimental design. The sample was selected using cluster random sampling. The data collection instrument used was a problem-solving ability test in the form of an essay test. Based on the results of calculations using the t-test, it was concluded that the Co-Op Co-Op Cooperative learning model had more influence on students' mathematical problem-solving abilities compared to the Missouri Mathematics Project.